Country Food Consumption Notices: Assessing Awareness and Preferences of Health and Risk Communication Messages in the Sahtú Region of the Northwest Territories - Brandow, Danielle (University of Waterloo, 2018)
Background: Country food consumption by Indigenous peoples is associated with improved nutrition, food security, and lower rates of chronic diseases (Kuhnlein, Burlingame, & Erasmus, 2013); however, these foods can also pose potential risks of exposure to contaminants such as mercury and cadmium (Berti, 1997). Elevated fish mercury concentrations in some lakes in the Sahtú region of the Northwest Territories (NWT) resulted in a series of consumption notices that suggested people limit their consumption of walleye, northern pike, and lake trout from specific lakes in the region (NWT, 2016). Therefore, as part of a health communication component was added. This component was designed to assess participants risk perceptions and awareness of current consumption notices and health messages, to provide baseline data to evaluate the impact of consumption notices, to determine how health messages are currently developed, and to make recommendations to create more targeted communication strategies. Objectives: The research objectives of this thesis are to: 1) Assess participants’ risk perceptions and awareness of current consumption notices and health messages; 2) Provide baseline data to evaluate the impact of consumption notices and health messages over time; 3) Understand how consumption notices and health messages are currently developed and communicated to communities by the Government of the Northwest Territories; and 4) Make recommendations that aim to improve and create more effective communication strategies with focus in the Sahtú Region of the Northwest Territories based on knowledge synthesized from terminology workshop(s), surveys, and interviews. Methods: This project involves a Health Messages Survey, two terminology workshops, community interviews, and stakeholder interviews. Participants were invited to take part in a Health Messages Survey where they were asked questions about their perceptions of contaminants, whether they had heard or seen consumption notices, in addition to their preferences for ...